Enforcement on movable objects and rights against the state and its authorities in the Republic of North Macedonia - Etemi-Ademi, Bukurije; Mamuti-Fazlia, Drita (Acta Universitatis Danubius. Juridica, 2024)
The application of enforcement actions varies between countries, mostly considering the subject that applies enforcement actions. In this context, we say that there are differences between the subjects and the stages of enforcement. In the countries where the permission phase is applied, the court decides on the merits of the proposal for enforcement, analysing whether the creditor had the right to request compulsory enforcement against the debtor specified in that document. Unlike the Western Balkan countries, RNM applies one-stage enforcement, where the bailiff determines the means and implements the enforcement. Based on preliminary research in the field of enforcement and the means that can be subjected to enforcement, and those that were excluded from enforcement, article 218 is a problematic point. For years there have been discussion in the professional literature, but also in the Supreme Court and the Constitutional Court of RNM. This research deals with the approach of restricting enforcement on state-owned objects and rights, creating a line of comparison between RNM and the countries of the Western Balkans. In the legislative aspect of the situation, it turns out to be similar in many states in the region. In most countries, there is a specific subject that allows the decision of implementation or non-implementation of enforcement, with the exception of the Republic of Kosovo, as a state with fewer legal rules dedicated to the limitation of enforcement. In the RNM, the President of the Court decides whether enforcement will be carried out or not. In Serbia and Montenegro, the judge of the case decides also for allowance, while in Bosnia and Herzegovina, applied restriction is at least within 0.3 percent of the total income planned in the budget of the debtors.